Overview of Determinants of Toddlers Nutritional Status in Sukajadi Village, Cisayong Subdistrict, Tasikmalaya Regency in 2022-2023 - Nuraeni, Irma; Sumarto; Ani Radiati; Ima Karimah; Dina Setiawati (JURNAL KESMAS DAN GIZI (JKG), 2025)
Monitoring the nutritional status of toddlers should be done regularly so that they do not experience health problems and are treated immediately. This study aims to describe the determinants of the nutritional status of toddlers in Sukajadi Village, Cisayong District, Tasikmalaya Regency. This research method is descriptive. The samples of this study were 60 mothers and toddlers aged 0-59 months in Sukajadi Village, Cisayong District, Tasikmalaya Regency. Data collection on nutritional status was carried out by anthropometric measurements. Characteristics of mothers and toddlers were conducted through questionnaire interviews. Macronutrient intake with a 24-hour recall interview and SQFFQ. The results showed that most mothers' education in 2022 and 2023 was high school / equivalent, namely 35% and 42%. Most of them were housewives, 85% in 2022 and 73% in 2023. 90% of mothers had a high level of knowledge in 2022 and 68% were in the moderate category in 2023. 78% of children under five were exclusively breastfed in 2022 and 57% in 2023. The majority of mothers practiced appropriate feeding patterns at 60% in 2022 and 72% in 2023. In 2022 and 2023, the energy deficit of children under five was 42% and 43%, the fat deficit was 47% and 48%, and the carbohydrate deficit was 50% and 53%, respectively. Although most children under five have normal and good nutritional status, there is still a high percentage of short and very short stature at 32% in 2022 and 43% in 2023. Further research is needed regarding the magnitude of the influence of these factors on nutritional status so as to provide appropriate interventions for prevention and handling.